Local labor - market effects of NAFTA in Mexico: Evidence from Mexican commuting zones - Danielle Trachtenberg (Inter-American Development Bank (IDB), 2019)
This paper estimates the effects of NAFTA on labor and wages in Mexico using a local labor-markets approach. While NAFTA offered greater export opportunities to Mexican firms that may raise employment, it also opened the door to increased import competition that may dampen employment gains. This paper finds that in the first decade of its existence, NAFTA had a net positive impact on domestic employment of 870,000 workers, an increase of 13.7%. Production workers in Mexican gained significantly, with employment increasing by 32.8%. The impacts of NAFTA varied by region, with employment gains accruing mostly to states in the northeast, northwest, and central east regions of Mexico, which traded more with NAFTA countries.
Keywords: F14; F16; F66; J23; 330; International trade; NAFTA; import competition; local labor markets